ANALYSIS OF SOCIAL PROBLEM IN A GOOD MAN IS HARD TO FIND BY FLANNERY O’CONNOR - Mohamad Hani (Universitas Muhammadiyah Makassar, 2019)
This study aims to describe the problems of social problems contained in the short story